PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN MOBIL SECOND DI SHOWROOM MOBCARS - DEVI ADE HERYANTI; Sari, Imelda (ANALISIS, 2026)
This study was conducted to analyze the influence of price variables on purchase decisions, test the influence of service quality on purchase decisions, and examine the influence of price and service quality simultaneously on purchase decisions. The research subjects consisted of consumers who had purchased a second car at the Mobcars showroom in the past one year, with a sample of 100 respondents. The sample was determined using non-probability sampling techniques, especially purposive sampling, by determining the number of samples using the Lemeshow formula. The research method used is a quantitative approach, where data collection is carried out through the distribution of questionnaires using Google Form, then the data obtained is analyzed with the help of Microsoft Excel software and SPSS version 26. The results of the study show that price has a significant influence on purchasing decisions. In addition, the quality of service also has a significant influence on purchase decisions. Simultaneously, price and service quality have a significant effect on purchasing decisions. It can be concluded that price and service quality play an important role in shaping consumer purchase decisions at the Mobcars showroom. Keywords: Price; Service Quality; Purchase Decision